Success indicators for an efficient utilization of cloud computing in healthcare organizations: Saudi healthcare as case study. (November 2021) - Alassafi, Madini O.
Highlights: This study was commenced by realizing the scope of wide scale adoption of cloud computing in the Saudi healthcare organizations to fulfil the increasing demand of modernizing healthcare services by the means of new technology adoption such as adoption of IoT, The result shows that users' attitude towards using technology, Data security, compliance and reliability of the cloud computing services are important determining factors in the adoption of cloud computing in Saudi healthcare organizations. The distinction in the finding regarding Data privacy and Data control in Saudi healthcare organizational context is a clear manifestation of the fact that there is need for policy formation for specific data protection legislation in Saudi Arabia Abstract: The population in Saudi Arabia is expected to reach 40 million by 2025. Consequently, healthcare information will become critical to manage. Despite the fact that adopting cloud computing in the Saudi healthcare organizations can facilitate cost reduction, capacity building, institutional interoperability, and get access to data analytics, the adoption rate is very low. Hence, a new model is proposed to adopt cloud computing in the Saudi healthcare organization. The novelty of this work comes from using a quantitative method to test users' attitudes, data security, data control, data privacy, compliance, and reliability influence on the cloud computing adoption intention in the context of Saudi Arabian healthcare organizations. Partial Least Squares (PLS) method based Structural Equation Modeling (SEM) was used for model development. About 160 respondents from the relevant health organizations participated. The result shows that the attitude towards using technology, data security, compliance, and reliability of the cloud computing services are important determining factors in the adoption of cloud computing in Saudi healthcare organizations. However, the distinction in the findings regarding Data privacy and Data control in the Saudi healthcare organizational context is a clear manifestation of the fact that there is a need for policy formation for data privacy, data control, and data protection legislation in Saudi Arabia. Therefore, raising awareness regarding the practice of data privacy and data control policies among IT managers is essential. Future study should use a more holistic and industry-specific framework such as the technology-organization-environment (TOE) framework to find new influencing factors from the domains of technological context, the organizational context, and the environmental context.